2014
DOI: 10.1177/0284185113506135
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of on-call radiology residents’ interpretation of 64-slice CT pulmonary angiography for the detection of pulmonary embolism

Abstract: The rate of discrepancy fell steeply between the second and fifth year of the residents training from 18.5% to 6.9%. Our study suggests that it is reasonable to have on-call radiology residents perform the preliminary interpretations of 64-slice CT for PE studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 11 publications
(19 reference statements)
0
17
2
Order By: Relevance
“…Studies has shown that there can be up to a 13% discrepancy rate between overnight radiologists and daytime faculty. [5][6][7] Increasing pressure is placed on hospital systems to provide 24-7 access to advanced imaging and to ensure that the results of urgent findings, such as PE, are rapidly and accurately communicated to the referring clinician. 8,9 However, providing rapid and accurate diagnostic imaging is increasingly difficult to sustain for many medical systems and radiology providers as utilization has expanded; for example, CTPA usage alone in the emergency setting has increased 27-fold over the past 2 decades.…”
Section: Introductionmentioning
confidence: 99%
“…Studies has shown that there can be up to a 13% discrepancy rate between overnight radiologists and daytime faculty. [5][6][7] Increasing pressure is placed on hospital systems to provide 24-7 access to advanced imaging and to ensure that the results of urgent findings, such as PE, are rapidly and accurately communicated to the referring clinician. 8,9 However, providing rapid and accurate diagnostic imaging is increasingly difficult to sustain for many medical systems and radiology providers as utilization has expanded; for example, CTPA usage alone in the emergency setting has increased 27-fold over the past 2 decades.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several previous studies addressing the degree of agreement between experienced radiologists and radiology residents’ interpretations of CTPA in an emergency context [ 23 25 ]. Our study shows a good IOA between the on-call radiology residents’ and the staff radiologists’ interpretation for PE with an overall agreement of 91.4% (kappa of 0.81).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, different outcome measures are used to assess improvements in diagnostic ability over time, including sensitivity/specificity, ROC-analysis and interreader agreement, making direct comparison among studies more difficult. There appears to be a general agreement that the amount of training is an important factor to achieve a high diagnostic accuracy (77,78,81), while the effects of previous radiologic experience on the ability to learn new radiologic methods have not been established (14,80). A few studies have shown a positive effect on the review time, but not on diagnostic accuracy (78,80).…”
Section: Pedagogical Aspectsmentioning
confidence: 99%
“…In studies on MRI in the detection of APE, primarily senior, experienced radiologists have reviewed the exams (65,(82)(83)(84)(85). However, in a clinical setting residents are commonly the primary reviewers (81). When introducing a new method, knowledge of the learning curves is of particular interest.…”
Section: Pedagogical Aspectsmentioning
confidence: 99%